Exchange Rates and Consumer Prices: Evidence from Brexit - Holger Breinlich; Elsa Leromain; Dennis Novy; Thomas Sampson (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies how the depreciation of sterling following the Brexit referendum affected consumer prices in the United Kingdom. Our identification strategy uses input-output linkages to account for heterogeneity in exposure to import costs across product groups. We show that, after the referendum, inflation increased by more for product groups with higher import shares in consumer expenditure. This effect is driven by both direct consumption of imported goods and the use of imported inputs in domestic production. Our results are consistent with complete pass-through of import costs to consumer prices and imply an aggregate exchange rate pass-through of 0:29. We estimate the Brexit vote increased consumer prices by 2:9 percent, costing the average household 870 per year. The increase in the cost of living is evenly shared across the income distribution, but differs substantially across regions.
Keywords: E31; F15; F31; 330; Brexit; exchange rate pass-through; import costs; inflation